2012
DOI: 10.1017/s1352465812000549
|View full text |Cite
|
Sign up to set email alerts
|

The Rescripting of Pain Images

Abstract: Index images of pain sufferers can be easily elicited and rescripted. Rescripting leads to remarkable reductions in emotion, cognitions and pain levels that are not attributable to image repetition. The significant reductions in pain were independent of reductions in emotion. The implications of these results for CBT approaches to pain management are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Many chronic pain patients, however, experience spontaneous, highly individual, pain-related images (Berna et al, 2012), and it might be beneficial for them to form their own personal images of pain reduction instead of visualizing a standard image. Indeed, one study found the rescripting of pain patients' most distressing pain image to a preferred, self-generated, image to be very beneficial (Philips and Samson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many chronic pain patients, however, experience spontaneous, highly individual, pain-related images (Berna et al, 2012), and it might be beneficial for them to form their own personal images of pain reduction instead of visualizing a standard image. Indeed, one study found the rescripting of pain patients' most distressing pain image to a preferred, self-generated, image to be very beneficial (Philips and Samson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is only in the last decade that clinical research concerning imagery has truly gathered momentum, leading to imagery being incorporated into established clinical treatments, such as cognitive behavioural therapy (CBT) [2]. CBT has an established evidence base in chronic pain management [3] and we propose that imagery-based CBT, which shows promise in acute and chronic pain [4], may offer a new treatment option for women with endometriosis-associated pain. We therefore sought to determine the prevalence, characteristics, and impact of pain imagery in women with endometriosisassociated pain.…”
Section: Dear Editormentioning
confidence: 99%
“…Patients who reported pain imagery (24% of sample) reported significantly higher levels of anxiety, depression, and catastrophizing than patients who did not report pain imagery (effect sizes: d = 0.76, 0.51 and 0.67, respectively). Finally, in a pilot randomized controlled trial of imagery rescripting in patients with pain, Phillips and Samson () showed that patients can change their pain‐related mental images and that this has important impacts on pain, anxiety, sadness, anger and appraisals of health threat and mental defeat. While this study did not investigate the long‐term stability of these changes, it is further evidence that there is an important relation between pain‐related mental images and psychological functioning.…”
Section: Introductionmentioning
confidence: 99%